Supply Chain Management During Crises and Its Impact on Organizational Financial Performance: An Empirical Study on the Financial Performance of UPS (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
The study investigates the effect of supply chain management (SCM) components during crises on the organizational financial performance of United Parcel Service UPS, Inc, one of the global leaders in logistics and shipping companies. The study explores three major independent variables, including the quality of information, the efficiency of logistics services (in terms of time and distance), and supplier relationship management. The research methodology is descriptive–analytical, and the data collection method involves a questionnaire given to a purposeful sampling of 50 branch managers of UPS Germany who held different managerial positions such as logistics manager, supply chain director, procurement officer, operations manager.Hypotheses were tested through simple linear regression analysis using EViews 12, and Cronbach's Alpha coefficient was computed to assess the internal consistency (reliability) of the measurement instruments. All variables demonstrated excellent reliability levels (α ≥ 0.89).The results reveal a statistically significant positive impact of all three SCM components on financial performance during crises such as the COVID-19 pandemic and geopolitical conflicts. Logistics services emerged as the most influential variable (r = 0.728; R² = 0.530; p < 0.001), followed by supplier relationship management (r = 0.620; R² = 0.384; p < 0.001), and information quality (r = 0.379; R² = 0.144; p < 0.01). Multicollinearity diagnostics confirmed the absence of problematic collinearity (VIF < 10).These findings underscore the strategic importance of logistics efficiency in crisis resilience and provide actionable insights for decision-makers in global logistics firms seeking to build more adaptive and financially robust supply chains.